The Prospect of Probiotics to Treat Metabolic Syndrome - Ramadhan, Andika Yusuf; Rosdiana, Dewi Selvina (Cell and BioPharmaceutical Institute, 2024)
Metabolic syndrome remains as a major health problem in the world today, with a prevalence of 23.4% in people aged 26-82 years. A high-fat, high-carbohydrate diet and lack of physical activity are considered as one of the triggers for metabolic syndrome. Dysbiosis is a condition where there is an imbalance between pathogenic and non-pathogenic bacteria in the human gut. Currently, an association has been found between dysbiosis and metabolic syndrome. Dysbiosis causes the generation of fermentation products in the form of active metabolites that can modulate hormones and other physiological functions. In metabolic syndrome, low-grade inflammation, energy metabolism, and disruption of the gut brain axis are thought to be the main mechanisms of the development of metabolic syndrome due to dysbiosis. Probiotics may be a promising therapeutic agent in the treatment of metabolic syndrome, by improving dysbiosis to eubiosis. Based on previously conducted clinical trials, it is currently known that probiotics can improve lipid profiles, fasting blood glucose, homeostatic model assessment for insulin resistance (HOMA-IR), vascular cell adhesion molecule 1 (VCAM-1), glucagon-like peptide-1 (GLP-1), peptide YY (PYY), and body mass index (BMI). However, the results found are still varied, so a dose ranging study is needed to determine the duration, bacterial composition and dose of probiotics as a therapeutic agent for metabolic syndrome. Keywords: insulin resistance, dysbiosis, gut-brain axis